Social Institutions Through the Lens of Ancient Indian Knowledge Systems (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Ancient Indian society is distinguished by its profound knowledge traditions and philosophical outlook that laid the foundation for cultural, educational and social development. The corpus of Vedas, Upanishads, Smritis, epics and Buddhist and Jain literature not only provided spiritual and intellectual guidance but also shaped the structure and functioning of major social institutions. The Gurukul system of education, The Varna and Ashram system, village panchayat, the institution of marriage and ethical framework of Dharma, Artha, Karma and Moksha all drew strength and legitimacy from these knowledge traditions. Such institution contributed to the cultivation of discipline, morality, responsibility and collective welfare within society. Furthermore, branches of knowledge such as Auyrveda, Mathmetics, astronomy, economics and political science, as exemplified in works like the Charak Samhita, Sulbha Sutras and Arthshastra provided a scientific and practical base for social life. They not only advanced intellectual pursuits but also offered sustainable solutions for health, governance and community well-being. The synthesis of science, philosophy and spirituality distinguished the Indian knowledge system as both holistic and deeply rooted in human values. This research paper examine how ancient Indian knowledge system contributed to the creation, sustenance and evolution of social institutions. It explores the role of education, ethics and collective practices in maintaining social harmony and analyzes how these traditions integrated spiritual liberation with material prosperity.